Keynote 1: Human health effects of non-thermal electromagnetic radiation - David O Carpenter (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch David O. Carpenter is a public health physician who serves as director of the Institute for Health and the Environment, a Collaborating Center of the World Health Organization, as well as a professor of environmental health sciences at Albany's School of Public Health. He previously served as Director of the Wadsworth Center of the New York State Department of Health, and as Dean of the University at Albany School of Public Health. Professor Carpenter, who received his medical degree from Harvard Medical School, has more than 435 peer-reviewed publications, 6 books and 50 reviews and book chapters to his credit. He is an Adviser of WHO in public health. His area of research is on Human health effects of environmental contaminants, including metals and organic compounds. The excessive exposure to both extremely low frequency and radiofrequency electromagnetic fields increase risk of several types of cancer, have adverse effects on human reproduction, alter at least some aspects of brain function and trigger in some people a syndrome of electrohypersensitivity. This syndrome consists of headaches, "brain fog", fatigue, tinnitus and a general sense of ill health. The major mechanism for all of these effects is likely to be the generation of reactive oxygen species, but more research on mechanisms is necessary.